History of the present time and historiography (Tempo e Argumento, 2012)
This article written in French was presented as a lecture at the opening of the First International Seminar -History of the Present Time, promoted by the Graduate Program in History of the University of Santa Catarina and ANPUH -Santa Catarina, held on November 7-9, 2011, in Florianópolis/Brazil. The author, in view of French historiography, introduces a collection of thoughts intended, on the one hand, to historicize the emergence of this historiographical field and, on the other hand, to infer on the problems and challenges in the History’s writing of the Present Time.
Keywords: history; present time; historiography